1981
DOI: 10.1021/bi00529a009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of dichlorobiphenyls by highly purified isozymes of rat liver cytochrome P-450

Abstract: Hepatic mixed-function oxidase metabolism of the ubiquitous pollutant polychlorinated biphenyls (PCBs) is implicated in their toxification and detoxification. We used dichlorobiphenyls (DCBs) as models to investigate the effect of the chloro substituent sites on this metabolism experimentally and by molecular orbital calculations. Reconstituted, purified cytochrome P-450 PB-B and BNF-B, the major terminal oxidase isozymes of this system, from phenobarbital (PB)- and beta-naphthoflavone (BNF)-induced rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 35 publications
5
74
0
1
Order By: Relevance
“…PB is metabolized by enzymes it induces, including P450s, and the sleeping time of rats decreases after a few days of continuous treatment. ␤NF-inducible rat P450 1A1 uses ␤NF as a substrate (Vyas et al, 1983), and some of the polychlorinated biphenyls in Aroclor are also substrates for the PB-and ␤NF-inducible P450s (Kaminsky et al, 1981). CCl 4 -induced isoprostane production is exacerbated by treatment of rats with INH or PB (Morrow et al, 1992), but this is a rather extreme case in that the only product is a reactive radical itself (⅐CCl 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…PB is metabolized by enzymes it induces, including P450s, and the sleeping time of rats decreases after a few days of continuous treatment. ␤NF-inducible rat P450 1A1 uses ␤NF as a substrate (Vyas et al, 1983), and some of the polychlorinated biphenyls in Aroclor are also substrates for the PB-and ␤NF-inducible P450s (Kaminsky et al, 1981). CCl 4 -induced isoprostane production is exacerbated by treatment of rats with INH or PB (Morrow et al, 1992), but this is a rather extreme case in that the only product is a reactive radical itself (⅐CCl 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies of the isoform-specific biotransformation of PCB congeners, particularly by the major Phenobarbital-inducible CYP2B isoforms and 3-methylcholanthrene-inducible CYP1A isoforms, e.g. (Kaminsky et al, 1981). Human CYP2B6 and rat CYP2B1 were the major isoforms for metabolism of PCB153 (Duignan et al, 1987;Ariyoshi et al, 1992), shown in figure 1, although it should be noted that PCB153 is relatively resistant to metabolism, and is therefore one of the more biologically persistent PCB congeners (Letcher et al, 2000).…”
Section: Formation and Properties Of Polychlorobiphenylols (Oh-pcbs)mentioning
confidence: 99%
“…Although oxidative metabolism of PCBs by rats has been studied extensively (Kato et al, 1980;Kaminsky et al, 1981), there has been only limited comparative analysis of in vivo metabolism of PCBs between hamsters and guinea pigs (Koga and Yoshimura, 1996). The results of the present study indicated that the tissue distribution profiles of PCB residues and OH-and MeSO 2 -CBs were largely dependent on the chlorination patterns classified into four groups.…”
Section: Discussionmentioning
confidence: 99%